Presumed Gadolinium Toxicity in Subjects With Normal Renal Function: A Report of 4 Cases - Semelka, Richard C; Commander, Clayton W; Jay, Michael; Burke, Lauren M B; Ramalho, Miguel (Investigative radiology, 2016)
The aim of this study was to examine and report 4 patients who developed symptomatology shortly after gadolinium-based contrast agent (GBCA) administration. History taking and targeted physical examination were performed on 4 subjects who reported development of new disease features within hours to 4 weeks of having received an intravenous administration of GBCA. Two subjects were assessed at 2 months (patient P2mo) and at 3 months (patient P3mo) after GBCA administration (early stage), and 2 subjects were assessed at 7 years (patient P7yr) and 8 years (patient P8yr) after having received GBCA administration (late stage). Clinical features were similar between subjects, and included central torso pain (all), peripheral arm and leg pain (all), clouded mentation (n = 2), and distal arm and leg skin thickening and rubbery subcutaneous tissue (one early and both late subjects). Gadolinium was detected as follows: in a 24-hour urine specimen, 1 month after disease development (18 μg/24 hours and 82 μg/24 hours in patients P2mo and P3mo, respectively); hair (0.0007 μg/g) and urine (0.0644 μg/g) samples, 7 years after disease development (late stage, patient P7yr); and saphenous vein sample, 8 years after disease development (0.27 ± 0.007 ng/62 mg sample) (late stage, patient P8yr). Gadolinium toxicity may occur in subjects with normal renal function. Central torso and peripheral arm and leg distribution pain were common features. Distal arm and leg skin thickening and rubbery subcutaneous tissue were seen in late stages. Clouded mentation is also common. Vigilance to identify additional cases and investigate strategies for prevention and treatment is warranted to increase even further the safety of a very safe diagnostic procedure, GBCA-enhanced magnetic resonance imaging.